2008
DOI: 10.1681/asn.2007050610
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impacts Access to Kidney Transplantation

Abstract: Current billing practices and mandates to report surgical outcomes are disincentives to surgical treatment of obese patients, who are at increased risk for longer hospital stays and higher complication rates. The objective of this study was to quantify the independent association between body mass index (BMI) and waiting time for kidney transplantation to identify potential provider bias against surgical treatment of the obese. A secondary data analysis was performed of a prospective cohort of 132,353 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
164
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(176 citation statements)
references
References 24 publications
7
164
0
5
Order By: Relevance
“…A recent study of adults with ESRD also found that obese patients were less likely to receive kidney transplants, particularly from living donors. 26 Given the known correlation between children's and parents' BMIs, a potential explanation for the low rate of transplantation among obese children is that their parents are less likely to be accepted as living donors. 14 Because parents account for almost 80% of living kidney donors for children, any limitation in parental donation could have an important effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of adults with ESRD also found that obese patients were less likely to receive kidney transplants, particularly from living donors. 26 Given the known correlation between children's and parents' BMIs, a potential explanation for the low rate of transplantation among obese children is that their parents are less likely to be accepted as living donors. 14 Because parents account for almost 80% of living kidney donors for children, any limitation in parental donation could have an important effect.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of listing for a deceaseddonor transplant and progression on the waiting list vary significantly by race/ethnicity, body mass index, socioeconomic factors, and geographic location (10,11). Numerous reports demonstrated that patients who are proactive and are able to navigate the processes involved to receive a transplant have significantly improved prognoses (12)(13)(14).…”
mentioning
confidence: 99%
“…In the adult population, there has been considerable debate about the access to transplantation according to BMI criteria, and in many national guidelines and centres specific policy limits (such as a BMI of 35 kg/m 2 ) are in place in an attempt to minimise the post-operative morbidity and mortality [11][12][13]. As yet, this does not appear to have translated into the paediatric setting and, indeed, it would be rather difficult to justify such a policy.…”
Section: Access To Transplantationmentioning
confidence: 99%